English language proficiency and initiatives of Malaysian universities - Mohd. Noor, Zainab; Sarudin, Isarji; Mohd. Aminudin, Zaidi (Medwell Journals, 2017)
The issue of employability of graduates of Malaysian universities has invited intense discussions in print and electronic media, particularly concerning graduate’s English language proficiency. This study presents the findings of a study investigating the initiatives of Malaysian universities in improving student’s English language proficiency. Data were collected based on a seminar participated by representatives from seventeen universities in Malaysia. Findings from the study revealed eight major initiatives to improve the English language proficiency of the students. English Language Enhancement Program (ELEP) was the most popular initiatives implemented by Malaysian universities. The study also discusses relevant challenges in implementing the initiatives. A systematic evaluation of the initiatives was recommended to ascertain that there is accountability and the initiatives are successful in meeting the intended objectives.